IoT-Based Smart Home Automation Design Analysis - Marthin Hotniel Marisi Arigatho Simbolon; Beni Satria; Ahmad Dani (Sean Institute, 2025)
The increasing need for comfort, energy efficiency, and home security has driven the development of an Internet of Things (IoT)-based smart home automation system. This study designs a smart home system using ESP32 as the main controller, integrated with a PIR sensor for intruder detection, a light sensor for automatic lighting control, a gas sensor for leak detection, and the Blynk application for remote monitoring. The main problem is the lack of affordable systems that integrate security and energy efficiency in real-time. The objective of this study is to develop a system that is cost-effective, responsive, and easy to use. Methods include hardware configuration, ESP32 programming, and testing in a residential simulation. The results show a PIR sensor detection accuracy of 95%, energy savings of up to 30% through automatic lighting control, and a Blynk notification reliability of 98%. This system offers an affordable solution to improve home security and energy efficiency.